Hypercyclic and supercyclic composition operator on some weighted sequence spaces - Srivastava, Vijay Kumar; Naudiyal, Ashish; Chandra, Harish (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.98 We consider a composition operator on some weighted ^p(λ) spaces and describe some of its basic properties including boundedness, closed range, surjectivity, hypercyclicity, and supercyclicity.